Pseudo-depth domain reverse time migration in VTI medium based on GPU parallel strategy - Xinwen, Zhang; Jianping, Huang; Zhiqiang, Jiang; Qingyang, Li; Zhenchun, Li (Frontiers in Earth Science, 2023)
As one of the main imaging methods, a lot of attention has been directed to reverse time migration anisotropic media. However, reverse time migration still faces cost and memory limitations, especially in imaging high frequencies. A coordinate transformation strategy in transversely isotropic media with a vertical axis of symmetry (VTI) was utilized to obtain high-resolution images useful for stratigraphic interpretation. The coordinate transformation converted traditional depth domain imaging into pseudo-depth domain imaging. In addition, this paper used the Graphics Processing Unit (GPU) parallel strategy and compared the imaging approach with the conventional acoustic isotropy method. By testing several models and field data, it concludes that Graphics Processing Unit parallel strategy can significantly improve the computational efficiency of imaging. The pseudo-depth domain method also has obvious advantages in computational time and memory consumption. Moreover, it is more reasonable when considering anisotropy for complex laminated layers.